Ms. Iffa Atlya Khairunnisa Pelatihan Vokasional untuk Mencapai Kemandirian Anak Berhadapan dengan Hukum: Penelitian pada Anak Berhadapan dengan Hukum di Sentra Handayani di Jakarta - Iffa Atlya Khairunnisa; Sundayani, Yana; Vonika, Nike (Politeknik Kesejahteraan Sosial Bandung, 2025)
This study aims to obtain an in-depth understanding of; 1) the implementation process of vocational training to achieve the independence of children in conflict with the law, including emotional, behavioral, and value-based independence; 2) supporting factors; and 3) challenges encountered during the vocational training process. This research employs a qualitative approach with a descriptive method. Data sources were selected using purposive sampling. Data collection techniques included in-depth interviews with five informants, comprising two children in conflict with the law, one social worker, and two vocational training instructors, field observations and document studies. Data analysis was conducted through data reduction, data presentation, and drawing conclusions. The results show that vocational training can serve to achieve independence and develop emotional, behavioral, and value-based independence in children in conflict with the law through the involvement of instructors and social workers, the process of independence formation, and strategies used by instructors to train independence. Factors supporting this process include the children's internal motivation, environment, parenting styles, and education. Challenges faced include children’s inconsistency in choosing training programs, lack of enthusiasm during training, and limited ability to adapt to productive activity routines.